WTO Agreement on Fisheries Subsidies: Is It Enough to Combat IUU Fishing in Asia-Pacific? - Jessica Ester (Journal of World Trade Studies, 2024)
Government subsidies on fisheries are supposed to provide welfare and development for the country. Nevertheless, some government subsidies contribute to a more fisheries crisis, including Illegal, Unreported, and Unregulated fishing (IUU Fishing). Subsidies in the fisheries sectors were estimated in 2018 to be as high as $35.4 billion worldwide, of which an estimated $22 billion qualified as harmful subsidies. Therefore, the World Trade Organization (WTO) in June 2022 adopted the Agreement on Fisheries Subsidies (AFS) to end prohibited fisheries subsidies. Henceforth, two-thirds of WTO members must deposit their instruments of acceptance to make the agreement viable. This normative legal research will utilize primary and secondary legal materials. The author intends to analyze these materials with a statutory and historical approach to examine (i) subsidy issues resulting in IUU Fishing, (ii) the AFS and its urgency, and (iii) whether AFS is sufficient to eliminate IUU fishing - in the Asia-Pacific region. This article argues that the AFS needs to be enforced to reduce harmful subsidies. However, the AFS is still not sufficient to thoroughly combat IUU fishing in the Asia-Pacific region, as it does not regulate certain issues such as overfishing and overcapacity, as well as banned fuel subsidies.